(untitled) (Journal of Parents and Teachers, 2013)
The school Jesüites Gràcia-Cabbage –Col·legi Kostka from Barcelona carries out an innovative experience based on the application of competences in the classroom. This initiative believes that a scientific method can be the source of the learning process and that it can be use to work competences (concretely all the core competences from Secondary Education). It is applied in from the eighth grade to the tenth of middle school, goes on with an Investigation Project in the eleventh grade and ends up with an Investigation, closer to a real one, in the last grades of Highschool. The students work not only their basic skills such as to be able to search information on Internet or from an adequate bibliography, to summarize, to outline and extract ideas; but also work complex skills and competences such as design experiments or investigations from different areas of knowledge (from social sciences or natural science to art or even literature). The main objective is to encourage the savoir-faire and the competence of learning to learn.